Currencies, capital flows and crises : a post Keynesian analysis of exchange rate determination - Harvey, John T. (London : New York : Routledge, 2009)
This book provides an explanation of exchange rate based on the premise that it is financial capital flows and not international trade that represents the driving force behind currency movements. In the book, the traditional approach is reviewed and critiqued and the alternative is then built by studying the psychology of the market and balance of payments questions.
Includes notes, bibliography and index (138-157)
nmn, 20/07/17
Loan
Keywords: Currencies; Capital flows; Exchange rate determination